MENJEJAKI AKSES TERHADAP KEADILAN DALAM KONFLIK AGRARIA: STUDI PADA WARGA MORO-MORO REGISTER 45 MESUJI LAMPUNG - Oki Hajiansyah Wahab; Muhammad Ridho (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: Agrarian conflictare inextricably linked to issues of injustice. There is a view that in equality in the agrarian conflicts can and should be resolved through legal measures, which were touted asthe establishmentand enforcement measures. By elaborating the idea of ​​access to justice within the framework of ROLAX and ROLGOM, as well as approach esthatare reviewed by the Theory access Ribot and Peluso, this paper seeks to study how access to justice can be achieve din agrarian conflicts. Of elaboration that access to justice can be the key to recovery in equalityin agrarian conflicts not only depend on the outcome of judicial decision simposing procedural-formal. The approach used is expected to read the constellation of the struggle for justice more broadly than just law enforcement measures and the establishment of formal, ie starting from the flow of benefits as well as the power relations that underliean access, to the quality of the legal system and achieving justice process based on the rule of law. With the scope of the analytical framework and approach, this paper focuses on the theoretical and conceptual depth. However this paperal so gives an over view and attempta simple analysis of the struggle of the Moro-moro citizens Register 45 Mesuji Lampung as acasestudy of the acquisition of access to justicein agrarian conflicts. Abstrak. Ada pandangan bahwa ketidakadilan dalam konflik agraria dapat diselesaikan melalui langkah yuridis sebagai langkah pembentukan dan penegakan hukum. Dengan mengelaborasi gagasan akses terhadap keadilan dalam kerangka Rolax dan Rolgom, serta pendekatan Teori Akses yang ditelaah oleh Ribot dan Peluso, tulisan ini berupaya untuk mempelajari bagaimana akses terhadap keadilan dapat dicapai dalam konflik agraria. Pendekatan yang digunakan diharapkan mampu membaca konstelasi perjuangan akan keadilan secara lebih luas daripada sekadar langkah pembentukan dan penegakan hukum formal, yaitu mulai dari adanya aliran manfaat serta relasi kekuasaan yang mendasari sebuah akses, sampai kualitas perangkat dan sistem hukum dari prosesmenggapai keadilan berdasarkan prinsip negara hukum. Tulisan ini berfokus pada pendalaman secara teoritis dan konseptualnya, tetapi tulisan ini juga berusaha memberikan gambaran dan analisis sederhana mengenai perjuangan warga Moro-moro Register 45 Mesuji Lampung DOI: 10.15408/jch.v4i2.3599